Cyclic behavior of joints assembled using prefabricated beams and columns with Engineered Cementitious Composite (ECC). (15th November 2021) - Li, Xiuling; Li, Yan; Yan, Meng; Meng, Weina; Lu, Xi; Chen, Kezhen; Bao, Yi
Highlights: Large-scale joints are assembled using prefabricated beams and columns with ECC. Assembled joint specimens achieve comparable cyclic behavior with cast-in-place specimen. ECC greatly enhances the load-carrying capacity and ductility of the joint specimens. Effects of bar splicer sleeves and connection position on the cyclic behavior are investigated. Abstract: This paper studies cyclic behaviors of joints assembled by prefabricated beams and columns made using Engineered Cementitious Composite (ECC). Five large-scale joint specimens were prepared and tested under cyclic loads until failure, including two joints made using conventional concrete and three joints made using ECC. One specimen was monolithically fabricated and used as the control. Three different assembling schemes were investigated to test the effects of bar splicer sleeves and connection position on the load-carrying capacity, failure mode, and ductility of the assembled joints. The results showed that ECC improved the load-carrying capacity and ductility of assembled joints. Employment of additional longitudinal bars and splicer sleeves enhanced the load-carrying capacity but compromised ductility because the failure mode was changed from flexural to shear failure. When ECC was used, the cyclic behavior was insensitive to connection position. This study is expected to promote design and engineering application of assembled joints.